Public accountant performance: The mediation role of organizational commitment - Mursal, Mursal; Wibisono, Chablullah; Ngaliman, Ngaliman; Dewi, Nolla Puspita; Basri, Basri (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine and analyze the direct influence of spiritual motivation, integrity, competence, organizational culture, locus of control, and organizational commitment on the performance of accountants at the Riau Islands Province Public Accounting Firm, and then indirectly test and analyze the influence of spiritual motivation, integrity, competency, organizational culture, and locus of control on accountant performance through organizational commitment. Research Methodology: The population in this study was 102 accountants using the census method, and the entire population was used as a sample. Quantitative data were collected using a questionnaire, and qualitative data were obtained by direct interviews with accountants. Results: From the research results it was found that of the six variables, the one that had the highest influence on performance was organizational commitment (t-value 6.321) and the lowest was spiritual motivation (t-value 2.507). Furthermore, spiritual motivation has the highest influence (t-value 21.893), and integrity has the lowest (t-value 3.467) on organizational commitment. Next, the position of organizational commitment plays the largest role in improving accountant performance and the smallest role is the spiritual motivation variable; the rest is influenced by other variables that were not examined in this study. Conclusions: The influence of dependent variables on independent variables is strong, as is the influence of dependent variables on intervening variables. In this research, all variables have a strong influence on the dependent and intervening variables. Limitations: The dependent variables of this study have not fully provided a definite role for organizational commitment on accountant performance; therefore, it is necessary to add other variables to clarify it.    Contribution: This study serves as a reference for developing an individual behavior model regarding individual characteristics, individual mechanisms, and what individuals produce in public accounting organizations that continue to experience changes in information technology from time to time in the context of reform for progress based on performance as an outcome.